Українське населення Прикам’я (на матеріалах Удмуртії): основні етапи формування й етнодемографічні характеристики - Чернієнко, Д. (Народна творчість та етнографія, 2009)
In this article the author strives for the diachronic observation of the formation, specifically, the Ukrainian studies in the Russian Prykamye (Udmurtia) in reference to the general stages and the ethnodemographic characteristics of the Ukrainian population in Udmurtia.